An infrared spectroscopic study of trifluoromethoxybenzene⋯methanol complexes formed in superfluid helium nanodroplets. Issue 44 (3rd November 2021) - Roy, Tarun Kumar; Mani, Devendra; Schwaab, Gerhard; Havenith, Martina
Abstract : The effect of CH3 → CF3 substitution on intermolecular interactions has been studied by comparing the IR spectra of trifluoromethoxybenzene⋯methanol and anisole⋯methanol. Abstract : We have studied the intermolecular complex formation between trifluoromethoxybenzene and methanol (CD3 OD) in superfluid helium droplets by infrared spectroscopy in the spectral range of 2630–2730 cm −1, covering the O–D stretches of methanol-d4 (CD3 OD). The cluster size associated with the observed bands is deduced from the variation of infrared intensity of a particular band with the partial pressures of trifluoromethoxybenzene and methanol. Quantum chemical calculations are performed at the MP2/6-311++G(d, p) level of theory to complement the experimental results. As a result, we have identified six different conformers of the trifluoromethoxybenzene⋯methanol intermolecular complex: three bound via O–H⋯O hydrogen bonds and the other three via O–H⋯π hydrogen bonds. Furthermore, to access the effect of fluorination on the methyl unit of anisole molecules, we compare the IR spectrum of trifluoromethoxybenzene (C6 H5 OCF3 )⋯methanol with our earlier reported spectrum of anisole (C6 H5 OCH3 )⋯methanol.